The Twelve absolutes of leadership - Burnison, Gary 1961- (New York McGraw-Hill, 2012)
Describes the twelve characteristics of effective leadership and provides advice on what is needed to develop these skills.
Lead -- Purpose -- Strategy -- People -- Measure -- Empower -- Reward -- Anticipate -- Navigate -- Communicate -- Listen -- Learn.
Includes index.
CSSP-8852, CSSP-8853 donated by The Asia Foundation Books for Asia.
KSSP-2731 donated by The Asia Foundation Books for Asia.
Keywords: Leadership